Pengkajian Dan Pengembangan Teknologi Gelombang Suara Dan Nutrisi Rumput Laut Pada Cabai Merah (Capsicum Annuum L.) - Yulianto Yulianto (Universitas Tadulako, 2008)
The aims of this assessment were to evaluate the adaptation and the development of sound wave technology and sea weed nutrition application on hot pepper. The assessment for evaluating the adaptation of sound wave technology was conducted on hybrid variety (TM99) of hot pepper in Soropadan, Temanggung Regency. The hot pepper has been applied with sound wave length 3500 – 5000 Hertz and sea weed nutrition. The development of sound wave technology on hot pepper was conducted on farm level at 5 locations. Coverage area of the development was 10 hectares each. The sound wave technology development was held at Songgom Lor, Tengki, Banjaratma, Lemah Abang, and Kemurang Kulon Villages, Brebes Regency. Result of the assessment indicated that yield of the sound wave technology and sea weed nutrition application on hot pepper was 11.92 t/ha, otherwise on farmer management without sound wave technology and sea weed nutrition application was 8.36 t/ha. The sound wave technology and nutrition could increase yield of hot pepper by 42.6 %. The increasing yield of hot pepper on the development level was 26.96 %. The yield of hot pepper applied with and without sound wave technology and sea weed nutrition were 8.55 t/ha and 6.65 t/ha respectively. R/C ratio with and without sound wave and nutrition applications were 2.23 and 1.79, respectively.